2012
DOI: 10.1007/s10526-012-9440-8
|View full text |Cite
|
Sign up to set email alerts
|

Host instar preference and functional response of Aphidius transcaspicus, a parasitoid of mealy aphids (Hyalopterus species)

Abstract: Aphidius transcaspicus Telenga (Hymenoptera: Braconidae: Aphidiinae) has been selected for use as a biological control agent against Hyalopterus pruni Geoffroy (Hemiptera: Aphididae) in prune orchards in California. In this study we focus on the host instar preference and functional response of A. transcaspicus. Host instar preference was determined using laboratory arenas by allowing female parasitoids to attack aphids on field-collected leaves of Prunus domestica L. supporting a natural range of H. pruni ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 59 publications
1
10
0
Order By: Relevance
“…Understanding the demographic composition of aphid populations under field conditions can guide classical biological control programs. For example, identifying predators or parasitoids that prefer nymphal aphid stages would have the greatest influence on λ (Latham & Mills, ). Retrospective analysis indicated that contributions from nymphal growth stages 2–3, 3–4, and 4 to adult (Figure B) collectively accounted for most of the variation in λ between feeding locations on flowers vs. leaves; reproductive adults had the single greatest positive contribution to λ.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the demographic composition of aphid populations under field conditions can guide classical biological control programs. For example, identifying predators or parasitoids that prefer nymphal aphid stages would have the greatest influence on λ (Latham & Mills, ). Retrospective analysis indicated that contributions from nymphal growth stages 2–3, 3–4, and 4 to adult (Figure B) collectively accounted for most of the variation in λ between feeding locations on flowers vs. leaves; reproductive adults had the single greatest positive contribution to λ.…”
Section: Discussionmentioning
confidence: 99%
“…Madadi et al . ; Carrillo & Peña ; Latham & Mills ), this technique has only recently been applied as a comparative tool in invasion biology (Dick et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…Whilst functional response techniques have been used extensively in biological control research to assess impacts of control agents (e.g. Madadi et al 2011;Carrillo & Peña 2012;Latham & Mills 2012), this technique has only recently been applied as a comparative tool in invasion biology . There is growing evidence that invasive species frequently exhibit higher functional response curve asymptotes (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Functional response can predict population dynamics and the prey suppression ability of a predator (Solomon, 1949;Murdoch & Oaten, 1975;Fern andez-Arhex & Corley, 2003), thus it may provide insight into the mechanisms of predator-prey interactions and how multiple predators affect prey populations (Holling, 1959(Holling, , 1966. Although the functional response has been widely applied in ecological studies to assess impacts of predators on prey populations, information about such interactions at a community level is limited (Madadi et al, 2011;Carrillo & Peña, 2012;Latham & Mills, 2012). Therefore, comparison of functional responses among combinations of predators can be a valuable approach to predict and assess multiple predator impacts on their shared prey populations (Kumar et al, 2014;Wasserman et al, 2016).…”
Section: Introductionmentioning
confidence: 99%